1979
DOI: 10.1136/oem.36.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity in a pulp and a paper mill in the United States: a ten-year follow-up.

Abstract: Two hundred and seventy-one men seen in 1963, who worked in a pulp and a paper mill, were followed up ten years later, in 1973. Death certificates were obtained for those who died. There did not appear to be any increased mortality in the group, nor was there any increased specific cause of death. A morbidity study of 200 men seen at both times did not show any differences in respiratory symptoms or prevalence of chronic non-specific respiratory disease. Analysis of pulmonary function showed little, if any, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
(3 reference statements)
0
17
0
Order By: Relevance
“…For the entire cohort ( 6.9 expected, SMR 116), and lymphosarcoma and reticulosarcoma (10 observed, 5.9 expected, SMR 169). All intestinal malignancies were of the colon; none were of the small intestine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the entire cohort ( 6.9 expected, SMR 116), and lymphosarcoma and reticulosarcoma (10 observed, 5.9 expected, SMR 169). All intestinal malignancies were of the colon; none were of the small intestine.…”
Section: Resultsmentioning
confidence: 99%
“…In the only published retrospective cohort mortality study of workers in a pulp and paper mill, Ferris et al (6) followed for 10 years a cohort of 271 pulp and paper mill workers identified as actively working in the mill in 1963. Although only 33 deaths occurred among these workers by 1973, the 33 deceased paper and pulp mill workers were reported to have an overall standardized mortality ratio of 126.…”
mentioning
confidence: 99%
“…'4 15 One previous observation has drawn attention to persistent hyperreactivity in subjects exposed acutely to unusually high levels of an irritating aerosol in whom symptoms developed within a few hours and continued for periods of four years or more and in whom bronchial wall biopsy showed inflammation.6 Consistent with this hypothesis is the fact that in two of the three subjects with hyperreactivity who underwent serial testing in this study, recovery to normal levels of reactivity has been observed after seven and 12 months. Verification ofthis possibility would require a longitudinal study with measurements of bronchial reactivity starting before hiring.…”
Section: Discussionmentioning
confidence: 99%
“…They are crushed finely in a shed that houses crushing machinery and then transferred to a laboratory building where they are weighed in a weighing room and transferred to another room where quantitative analysis is undertaken. The minerals are dissolved in concentrated solutions of hydrochloric, hydrofluoric, nitric, perchloric, and sulphuric acids including "aqua regia", after which they are "digested" by heating them in open beakers in fume cupboards for [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] hours. The resulting solutions are then submitted for atomic absorption (AA) and inductive coupled plasma (ICP) spectrometry in separate adjacent rooms in the laboratory building.…”
mentioning
confidence: 99%
“…Each year in the pulping process was associated with a 5-8 ml decrease in FEV, (p = 0 08) and a 7-2 ml decrease in FVC (p = 0-04) (model A, 7 9 ml/y, p = 0 12) than work in the sulphite mill (-4-2 ml/y, p = 0 35) or work in the chlorine operation (-57 ml/y, p = 037).…”
Section: Regression Analysesmentioning
confidence: 99%